2016
DOI: 10.1051/epjconf/201612301007
|View full text |Cite
|
Sign up to set email alerts
|

Proton emission – new results and future prospects

Abstract: Abstract. Proton emission is the radioactive decay mode that is expected to determine the limit of observable proton-rich nuclei for most elements. Considerable progress has been made in the study of proton-emitting nuclei since the first observation of direct proton emission nearly 50 years ago. This has led to improvements in our understanding of this decay process and provided invaluable nuclear structure data far from the valley of beta stability. The rapid fall in half-lives with increasing neutron defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…4 of that paper the two-proton decay is seen to proceed as a sequential emission. Instead, in the two-proton decay of 31 Ar [81] the simultaneous emission of the two protons fits the data well. But sequential decays might also describe the experimental data.…”
Section: Two-proton Decaymentioning
confidence: 78%
See 1 more Smart Citation
“…4 of that paper the two-proton decay is seen to proceed as a sequential emission. Instead, in the two-proton decay of 31 Ar [81] the simultaneous emission of the two protons fits the data well. But sequential decays might also describe the experimental data.…”
Section: Two-proton Decaymentioning
confidence: 78%
“…Detailed review of the experimental developments leading to the present status of proton radioactivity can be found in Refs. [29,30,31]. The first developments in the theoretical treatment of this subject has been reviewed in Refs.…”
Section: Systematic Studies Of Proton Radioactivity and Nuclear Struc...mentioning
confidence: 99%
“…Ground-state proton emission [6][7][8][9][10][11] was found in the early 1980s via the discovery of 151 Lu [12], shortly followed by the identification of 147 Tm [13] (T1 /2 = 0.58(3) s [14]). To date, approximately 50 [10] cases of proton emission are known between 108 I [5] and 185 Bi [15]; the only odd-Z element in between without observed proton emission is promethium.…”
mentioning
confidence: 99%
“…Detailed reviews of the experimental proton-emitter data can be found, for example, from Refs. [10][11][12][13][14].…”
mentioning
confidence: 99%